17-Italian Foot Function Index with numerical rating scale: Development, reliability, and validity of a modified version of the original Foot Function Index. Issue 1 (March 2015) - Venditto, Teresa; Tognolo, Lucrezia; Rizzo, Rosaria Sabrina; Iannuccelli, Cristina; Di Sante, Luca; Trevisan, Mauro; Maggiolini, Francesca Romana; Santilli, Valter; Ioppolo, Francesco
Highlights The painful foot and ankle conditions limit the activities of daily living and are the leading cause of immobility and disability. FFI is one of the most frequently used self-reported questionnaires that is used across national and international clinical and research communities. The adapted 17 Italian Foot Function index is a reliable and valid outcome measure that showed more specific and sensitive properties than a generic questionnaire such as the LEFS.